The effect of ion accumulation owing to water recycling on flotation performance - Dzingai, Mathew (Department of Chemical Engineering, 2020)
With the drive to reduce water usage globally, the mining sector must reassess its water usage as it has in the past contributed greatly to environmental degradation due to effluent discharge, tailing disposal and process water seepage into the water-table. Mineral beneficiation entails different unit operations; amongst them is froth flotation. Froth flotation is a multifaceted complex process which is water intensive and to manage water usage, the global mining industries are now recycling water. The recycled water may contain deleterious ions that affect the mineral surface, pulp chemistry and reagent action, hence the need to establish whether threshold concentrations exist beyond which the flotation performance will be adversely affected. This is of paramount importance in informing appropriate recycle streams and allowing simple, cost-effective water treatment methods to be applied. To better understand the influence of water recycling in flotation, a low-grade Cu-Ni-PGM sulphide ore was used. This study investigated the effects of increasing ionic strength as well as increases in specific ion concentrations to determine whether these selected ions had beneficial or deleterious effects on the flotation process. Copper and nickel were the target metals, floated as chalcopyrite and pentlandite, respectively. Their recovery and grade under different conditions was used as a measure to quantify whether a threshold ion concentration existed. The key performance indicators used were: (a) water recovery, (b) solids recovery, (c) valuable metal recovery, (d) grade of the recovered concentrates and (e) electrical conductivity. While a complex background water chemistry of 3 SPW was maintained for the spiking tests, ion spiking was intended to mimic the recycling of water and the most prevalent ions which would likely be recycled and therefore accumulated, such ions as: Ca2+, Mg2+, NO3 - , SO4 2- and S2O3 2-. These ions were chosen based on speculation from relevant literature that they might impact the flotation performance due to their influence on pulp chemistry and reagent interaction. This was achieved by conducting sequential batch flotation and electrical conductivity (EC) tests. Batch flotation tests were performed to investigate the effect of different ionic strength conditions on the overall flotation performance. The same ionic strengths and spiking concentrations were used for froth (or foam) column studies with a focus on tracking the ion concentration distribution between the froth and the slurry (or solution) by means of measuring the EC of each of the froth and the pulp (solution) phases. The differences implied whether the ions were selectively concentrated at the air-water or solids-water interphases in a 3-phase system or likewise at the v bubble surface or within the solution for a 2-phase system. This distribution of ions was linked to the other key performance indicators. Increasing ionic strength; 3, 5 and 10 SPW respectively, resulted in an increase in water recovery in the order 3 SPW < 5 SPW < 10 SPW, indicating an increase in froth stability due to inhibition of bubble coalescence at high ionic strength. There was, however, no significant effect on the valuable metal recovery. Most of the nickel was recovered in the copper circuit which was expected as on-site conditions were not maintained at the laboratory scale, no lime was added to adjust the pH in the copper circuit and an EDTA chelating agent was not included in the nickel circuit. Spiking 3 SPW with 800 ppm Ca2+ results in considerably higher water recovery per unit solids recovered compared to 3 SPW, 5 SPW, 400 ppm Ca2+, 350 ppm Mg2+, 700 ppm Mg2+. 400 ppm Ca2+ resulted in the highest copper and nickel grade and was deemed the threshold for this study while for Mg2+ threshold lies outside of the range considered for this study. 10 SPW shows a decrease in the copper and nickel grade while the copper and nickel recoveries were not significantly impacted. The presence of the Ca2+ and Mg2+ at high concentrations leads to gangue activation which as a consequence will result in decreased grade. 880 ppm NO3 - gave the highest copper and nickel grade compared to 3 SPW while increasing the S2O3 2- from 60 to 78 ppm resulted in an increase in nickel grade. 1200 ppm SO4 2- and 880 ppm NO3 - were deemed the threshold concentration for these anions, above which the flotation performance declines, while for S2O3 2- the threshold lay outside the range considered for this study. This study has shown that the accumulation of ions within plant water, owing to recycling, is, in general, beneficial to flotation. This study has also shown that there is a concentration for each ion beyond which it is no longer beneficial to flotation. While this finding is clearly ore and ion dependent, it gives an indication as to the need for water treatment and considering the threshold concentrations found, may direct operations to suitable treatment methods for their systems.